Optimization of gradient reversed phase high performance liquid chromatography analysis of acetaminophen oxidation metabolites using linear and non-linear retention model - Vanova, Jana; Malinak, David; Andrys, Rudolf; Kubat, Miroslav; Mikysek, Tomas; Rousarova, Erika; Musilek, Kamil; Rousar, Tomas; Cesla, Petr (Journal of chromatography. A, 2022)
Acetaminophen (paracetamol, APAP) is one of the most widely used drugs worldwide. Unfortunately, its overdose, which is caused by predominant oxidation of APAP, can lead to acute liver injury. In liver, oxidized APAP is conjugated with glutathione, leading to APAP-glutathione conjugate, which is metabolized to APAP-cysteine and APAP-N-acetylcysteine conjugates. Thus, all of those compounds could be used to monitor APAP metabolism in the overdosed patients. To date, only a limited number of rapid and accurate methods have been reported for the assessment of APAP oxidation metabolites using simple instrumentation, and thus this work was aimed at developing a fast and convenient gradient HPLC-UV/MS method. For this purpose, APAP conjugates with glutathione, cysteine, and N-acetylcysteine were synthesized, purified by preparative liquid chromatography, and characterized by NMR and high-resolution mass spectrometry. The gradient elution conditions were optimized using the window diagram approach and the effects of mobile phase composition and additives on separation and detection sensitivity were evaluated using two, i.e., linear and non-linear isocratic retention models. Quantitative parameters of the developed method were evaluated and the effectiveness, sensitivity, and specificity of the method were demonstrated on the analysis of human kidney HK-2 cell lysates, confirming the suitability of the method for routine use in studies on APAP toxicity.
Keywords: Acetaminophen; Chromatography, High Pressure Liquid; Isocratic retention models; Optimization; Chromatography, Liquid; Humans; chromatografie kapalinová; Chromatography, Reverse-Phase; Acetylcysteine; acetylcystein; lidé; Acetaminophen-S-conjugates; Window diagram; Metabolites; vysokoúčinná kapalinová chromatografie; Gradient elution; chromatografie s reverzní fází; paracetamol